Parametrični vplivi na kakovost in zanesljivost merilnega vezja: Učbenik - Matko, Vojko (University of Maribor Press, 2022)
Parametric Influences on the Quality and Reliability of a Measuring Circuit: Textbook. The content covers influences of different parameters on the quality and reliability of measuring circuit. The parametric approach gives a very accurate the study of the influence of circuit parameters, relevant quantities as well as the optimization of the measurement circuits in terms of the “ECO (Ecology) design”. This is prescribed by the European Directive 2009/125 /CE and sets the framework for setting the ecodesign requirements for products related to minimization of electricity consumption. In compliance with this directive, while reducing the energy consumption of individual circuits, we must also check the quality and reliability of operation, which, in this textbook, is focused on the measurement uncertainty of measurement circuits. Important goals of the parametric approach are to obtain information on the magnitude of individual parametric influences to improve quality in terms of improving measurement uncertainty while reducing a power consumption and, above all, to obtain information on how to improve the circuit. The content of this publication is also generally applicable to other subjects of general electrical engineering.